Pengaruh Media Sosial Terhadap Pembentukan Akhlak Peserta Didik Dalam Perspektif Pendidikan Islam - Sidik, Fajar; Wardiman, Zulkifli (Institut Muslim Cendekia, 2026)
The digital disruption era positions social media as a dominant factor influencing student morality, making character building a crucial challenge for Islamic Education. This study aims to analyze the influence of social media on student morality and to formulate integrative coaching strategies based on Islamic values. The methodology employed is descriptive qualitative with a Systematic Literature Review (SLR) approach, examining 16 studies articles from the 2023-2025 period. The results indicate that social media has a significant influence, reaching up to 66%, on behavioral changes. Negative impacts are manifested in the erosion of etiquette and destructive behavior, while positive impacts are seen in its use as a medium for dawah. The novelty of this research lies in the synthesis of a moral development model that synergizes family supervision (ri’ayah), educators' exemplary behavior (uswah hasanah), and digital literacy based on tazkiyatun nafs. The implications of this study emphasize the importance of reconstructing a technology-adaptive moral curriculum to build students' spiritual immunity in cyberspace. This holistic strategy is expected to serve as a foundation for schools and parents in minimizing the negative impacts of technology without hindering responsible access to information.